PENGARUH MEDIA AUGMENTED REALITY ‘SPINNING WHEEL’ BERBASIS ASSEMBLR STUDIO TERHADAP KOSAKATA BAHASA INGGRIS ANAK DI TAMAN KANAK-KANAK VILLA BETA KOTA PADANG - Zelva Melani; Rismareni Pransiska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low mastery of English vocabulary among early childhood children remains a problem influenced by the limited availability of interesting learning media and the minimal use of technology. This study aims to determine the effect of the use of Assemblr Studio-based Augmented Reality ‘Spinning Wheel’ media on the English vocabulary of early childhood children at Villa Beta Kindergarten, Padang City. The study used a quantitative approach with a pre-experimental method through a One Group Pretest Posttest Design. The research subjects were 15 children who were determined using a saturated sampling technique. The research instrument was in the form of oral and behavioral tests compiled based on indicators of early childhood language development and validated by experts. Data analysis was carried out using parametric statistical tests with the help of SPSS version 29, including normality tests and Paired Sample T-tests. The results showed a significant increase between pre-test and post-test scores with a significance value of <0.05. Thus, the Assemblr Studio-based Augmented Reality ‘Spinning Wheel’ media has a significant effect in improving English vocabulary mastery among early childhood children.